(untitled) (Gaceta Técnica, 2026)
Transportation infrastructure is crucial for economic and social development, especially in countries like Ecuador, where its condition significantly impacts connectivity, the supply chain, and the population’s standard of living. This study analyzed the use of recycled rubber particles from end-of-life tires as a partial replacement for fine aggregate in the production of concrete pavers. Mixtures with substitution rates of 3%, 5%, 10%, 12%, and 20% were prepared and evaluated using standardized tests to measure compressive strength and abrasion resistance. The findings indicated a progressive reduction in compressive strength as the amount of rubber increased, yielding values ​​between 38,94 MPa and 27,36 MPa. The mixture with 12% rubber achieved a compressive strength of 36,10 MPa, exceeding the minimum requirement of 35 MPa. During the abrasion test, the paving stones exhibited a chord length of 25 mm, meeting national standards and surpassing the performance of traditional paving stones. Statistical analysis, after removing 13,09% of outliers, confirmed that the data were normally distributed (p = 0,056). This ensures with 95% confidence that a randomly selected paving stone will have a compressive strength between 36,12 MPa ± 2 × 0,301 MPa